Portfolio manager ownership and fund performance - Khorana, Ajay; Servaes, Henri; Wedge, Lei (Journal of Financial Economics, 2007)
This paper documents the range of portfolio manager ownership in the funds they manage and examines whether higher ownership is associated with improved future performance. Almost half of all managers have ownership stakes in their funds, though the absolute investment is modest. Future risk-adjusted performance is positively related to managerial ownership, with performance improving by about 3 basis points for each basis point of managerial ownership. These findings persist after controlling for various measures of fund board effectiveness. Fund manager ownership is higher in funds with better past performance, lower front-end loads, smaller size, longer managerial tenure, and funds affiliated with smaller families. It is also higher in funds with higher board member compensation and in equity funds relative to bond funds. Future performance is positively related to the component of ownership that can be predicted by other variables, as well as the unpredictable component. Our findings support the notion that managerial ownership has desirable incentive alignment attributes for mutual fund investors and indicate that the disclosure of this information is useful in making portfolio allocation decisions.